Rifts and passive margins : structural architecture, thermal regimes, and petroleum systems - Nemčok, Michal (Cambridge University Press, 2016)
This is a comprehensive synthesis of state-of-the-art information on vitally important hydrocarbon habitats for advanced geology students and researchers, exploration geoscientists, and petroleum managers.